Bireociclib plus fulvestrant for HR+/HER2- advanced female breast cancer progressed on or after endocrine therapy: phase 3 BRIGHT-2 study interim analysis - Jiayu Wang; Qingyuan Zhang; Huiping Li; Zhongsheng Tong; Quchang Ouyang; Huihui Li; Yuee Teng; Biyun Wang; Tao Sun; Jingfen Wang; Wei Li; Zhaofeng Niu; et al. (Nature Communications)
Abstract The BRIGHT-2 study (NCT05077449) is a randomized, double-blind, placebo-controlled, phase 3 trial evaluating the efficacy and safety of bireociclib plus fulvestrant (BF) vs. placebo plus fulvestrant (F) in Chinese female patients with hormone receptor-positive (HR+)/HER2-negative (HER2-) advanced breast cancer (ABC) who had progressed on or after prior endocrine therapy (ET). Interim results were analyzed after 70% of progression-free survival (PFS) events across 64 centers in China between December 8, 2021, and March 28, 2023. Patients were randomized (2:1) to receive BF or F, with stratification based on visceral involvement (yes/no) and resistance to prior primary or secondary ET. As the primary outcome, PFS was significantly prolonged in the BF group (n = 204) (12.94 months; 95% CI: 11.07–not reached) compared to 7.29 months (95% CI: 5.45–11.04) in the F group (n = 101) (hazard ratio, 0.56; 95% CI: 0.39–0.80; p = 0.001). The objective response rate in the BF group was 39.7% in the intention-to-treat population. Grade ≥3 adverse events were more frequent in the BF group (64.7%) than in the F group (18.8%), with neutropenia, leukopenia, and anemia being the most common. These findings suggest that BF is a promising therapeutic option for patients with HR+/HER2- ABC following ET failure.